A Study on the China-Laos Railway’s Economic and Strategic Significance: https://doi.org/10.69692/SUJMRD1001115 - Yan, Xuchong; Qiu, Zhimei (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
To analyze the economic and strategic significance of the China-Laos Railway, this paper will examine its impact on both China and Laos from their respective perspectives during the construction of the railway. The results show that the China-Laos Railway will significantly improve transportation efficiency in Laos, promoting rapid economic and social progress and development; The China-Laos Railway will be fostering economic development and cooperation among the countries and regions along the railway; Simultaneously, the successful construction of the China-Laos Railway has showcased China's prowess in high-speed railway construction to the international community, setting a positive example for China's future expansion into new high-speed railway markets; The successful construction of the China-Laos Railway, along with its later plans to connect ports on the west coast of Thailand and Malaysia, will facilitate the opening of new Indian Ocean ports in China's southwest, ensuring the secure supply of energy transportation; Moreover, The China-Laos Railway will also bolster China's geopolitical influence in ASEAN, deepen economic and political cooperation between China and ASEAN countries, and play a significant role in advancing the implementation of China's Belt and Road Initiative.